The perils of federalism race, poverty, and the politics of crime control - Miller, Lisa Lynn.; Oxford eBooks (Oxford : Oxford University Press, 2008)
Much of the existing research on race and crime focuses on the manipulation of crime by political elites or the racially biased nature of crime policy. However, Miller's study zeroes in on the political and socio-legal institutions and actors that drive these developments and their relationship to the politics of race and poverty.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Crime prevention -- United States -- Citizen participation; Crime prevention -- Pennsylvania -- Citizen participation; Federal government -- United States; Pressure groups -- United States; Pressure groups -- Pennsylvania; African Americans -- Crimes against -- Prevention -- Citizen participation; Poor -- Crimes against -- United States -- Prevention -- Citizen participation; Electronic books